PCNA and Rnh1 independently participate in the protection of mitochondrial genome against UV-induced mutagenesis in yeast cells - Martyna Latoszek; Katarzyna Baginska-Drabiuk; Ewa Sledziewska-Gojska; Aneta Kaniak-Golik (Scientific Reports, 2024)
Abstract In Saccharomyces cerevisiae cells, the bulk of mitochondrial DNA (mtDNA) replication is mediated by the replicative high-fidelity DNA polymerase γ. However, upon UV irradiation low-fidelity translesion polymerases: Polη, Polζ and Rev1, participate in an error-free replicative bypass of UV-induced lesions in mtDNA. We analysed how translesion polymerases could function in mitochondria. We show that, contrary to expectations, yeast PCNA is mitochondrially localized and, upon genotoxic stress, ubiquitinated PCNA can be detected in purified mitochondria. Moreover, the substitution K164R in PCNA leads to an increase of UV-induced point mutations in mtDNA. This UV-dependent effect is highly enhanced in cells in which the Mec1/Rad53/Dun1 checkpoint-dependent deoxynucleotide triphosphate (dNTP) increase in response to DNA damage is blocked and RNase H1 is lacking, suggesting that PCNA plays a role in a replication damage bypass pathway dealing with lesions in multiple ribonucleotides embedded in mtDNA. In addition, our analysis indicates that K164R in PCNA restricts mostly the anti-mutagenic Polη activity on UV-damaged mtDNA, whereas the inhibitory effect on Polζ’s activity is only partial. We also show for the first time that in conditions of dNTP depletion yeast Rnh1 neutralizes deleterious effects of ribonucleotides for mtDNA replication, thereby preventing the enhanced instability of rho + mitochondrial genomes.